2021
DOI: 10.3390/children8111051
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Subcutaneous and Intraperitoneal Instillation of Local Anesthetics on Postoperative Pain after Laparoscopic Varicocelectomy: A Randomized Controlled Trial

Abstract: Background: The main goal of the present randomized clinical trial was to investigate the effects of subcutaneous administration of two different local anesthetics at trocar incision sites at the abdominal wall in combination with intraoperative intraperitoneal instillation of local anesthetics, on the character of postoperative pain, in adolescents who underwent laparoscopic varicocelectomy. Methods: A total of 60 patients with a median age of 16 years, who received laparoscopic varicocele repair, were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Pre-emptive analgesia can be used to prevent a pain signal from the surgical wound starting from the very first skin incision. These findings have been confirmed in previously published studies on pre-emptive analgesia in different surgical conditions [ 11 , 12 , 13 ]. The aim of this double-blinded, randomized, placebo-controlled trial was to determine whether children undergoing otolaryngological procedures (adenoidectomy, tonsillectomy, or adenotonsillectomy) benefit from pre-emptive analgesia in the postoperative period.…”
Section: Introductionsupporting
confidence: 87%
“…Pre-emptive analgesia can be used to prevent a pain signal from the surgical wound starting from the very first skin incision. These findings have been confirmed in previously published studies on pre-emptive analgesia in different surgical conditions [ 11 , 12 , 13 ]. The aim of this double-blinded, randomized, placebo-controlled trial was to determine whether children undergoing otolaryngological procedures (adenoidectomy, tonsillectomy, or adenotonsillectomy) benefit from pre-emptive analgesia in the postoperative period.…”
Section: Introductionsupporting
confidence: 87%
“…Zenon Pogorelic and colleagues performed a randomized controlled trial on the effect of subcutaneous injection at trocar incision sites and intraperitoneal instillation of local anesthetics on postoperative pain after laparoscopic varicocelectomy in adolescents. Compared to the control group, the level of postoperative pain was significantly lower in patients who received local anesthetics intraoperatively [7].…”
mentioning
confidence: 71%
“…A randomized, double-blind, placebo-controlled study in which 36 adult patients underwent breast cancer surgery exhibited a decrease in the incidence and intensity of chronic pain following the procedures, with the use of perioperative intravenous lidocaine (bolus of IV lidocaine 1.5 mg/kg followed by continuous infusion of lidocaine at 1.5 mg/kg/h). It is well-known that application of lidocaine at the site of surgical incision reduces postoperative pain [ 23 ], but clinical evaluations suggested that the use of intravenous lidocaine therapy in this way has beneficial effects on pediatric postoperative pain, the opioid demand and the sense of well-being of children, especially during the 24 h postoperatively [ 24 ]. Sun et al published a meta-analysis of randomized controlled trials where they explored the use of systemic lidocaine for postoperative analgesia and recovery after abdominal surgical procedures [ 25 ].…”
Section: Discussionmentioning
confidence: 99%